A modern approach to the treatment of plaque psoriasis - Drvar Daniela Ledić; Vlahinić Tomislav; Maleš Željan; Turčić Petra; Čeović Romana (Acta Pharmaceutica)
Psoriasis is a common chronic inflammatory skin disease which affects 0.5–1 % of children and 2–3 % of the adult population. In Croatia, 1.6 % of the population suffer from psoriasis. Distribution of the disease is bimodal, with the first peak at the age of 20–30, and the second at the age of 50–60. The etiopathogenesis of the disease is multifactorial, the key factors being genetic predisposition combined with immunological disorders, environmental factors and skin barrier damage. There are several clinical variants of the disease. The main signalling pathways in psoriasis include TNF-α, IL-23 and IL-17. Topical agents are used for the treatment of the mild form, and the systemic conventional therapy is used for the treatment of moderate to severe forms of the disease. In cases where’s no response, or intolerance or contraindications are present, new targeted medications are to be administered. Development in the field of immunogenetics of psoriasis leads to personalized medicine.